Persuasion ability in children from 6 to 12 years old: Relations to cognitive and affective theory of mind - Barajas, Carmen; Linero, María-José; Alarcón, Rafael (Frontiers in Psychology, 2022)
This study analyzes the relation between cognitive and affective components of theory of mind (ToM) in school aged children and persuasion abilities. 143 normotypical school children aged 6 to 12 were administered cognitive and affective ToM tasks and one persuasion production task. A set of regression models showed that only the affective ToM component can predict both the persuasion total scores and all its indicators' scores. Children with a greater ability to attribute emotional mental states do not only produce a wider variety of persuasive arguments but also arguments focused on the persuadee and those with mental-related content. Both Hidden Emotion and Belief-Emotion (negative) tasks have been predictive of persuasion total scores. This study provides data on specific contribution of cognitive ToM and affective ToM independently on indicators of variety and quality of persuasive arguments indenpendently.